Prevalence of stocked whitefish in River Kemijoki, Finland, inferred by micro X‐ray fluorescence analysis of otoliths. (15th May 2020) - Finnäs, Viktor; Lill, Jan‐Olof; Heimbrand, Yvette; Blass, Martina; Saarinen, Timo; Lahaye, Yann; Jokikokko, Erkki; Hägerstrand, Henry
Abstract: Micro X‐ray fluorescence (µ‐XRF) analysis of otoliths was evaluated as a method to estimate the proportion of stocked one‐summer‐old whitefish Coregonus lavaretus L. in catches of adult fish ( n = 20) ascending the River Kemijoki to spawn. Laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) analysis was applied as control. Polished otoliths were scanned with µ‐XRF to obtain strontium maps that were used to infer visually the provenance of the whitefish. Thirteen of the fish showed signs of being stocked as one‐summer‐old fingerlings. LA‐ICP‐MS was applied to determine the elemental composition in a spot outside the core of the otolith. The results were largely consistent with the visual inspection of the µ‐XRF mapped otoliths. In conclusion, µ‐XRF mapping successfully identified whitefish stocked as one‐summer‐old fingerlings. The vast majority of whitefish returning to the River Kemijoki to spawn were stocked fish.